Momongu Kambungu Program Through White Copra Processing in Totopo Village, Gorontalo Regency - Yusuf, Taufiq Ismail; Tansa, Salmawaty; Tolago, Ade Irawaty (ELDIMAS: Jurnal Pengabdian Pada Masyarakat, 2024)
Community Service Activities are an effort by Gorontalo State University so that the Tridharma of Higher Education can be implemented by raising the main theme "Momongu Kambungu" which means "Building a Village" from the potential of existing natural resources. . Based on the results of the survey conducted, the potential of Tolotio village is abundant coconut production, but currently it still uses traditional processing that is of low quality and has a high water content. The purpose of this service is to provide insight and knowledge about the correct processing of white copra and meets export standards. The Community Service activity method uses lecture and demonstration methods. The steps of the activity are lectures to explain how to process white copra using a greenhouse, an advantage compared to the previous conventional processing of black copra. then continued with a demonstration of how to process white copra with a greenhouse system. Kegiatan Pengabdian adalah suatu upaya Universitas Negeri Gorontalo agar Tridarma Perguruan Tinggi dapat terlaksana dengan mengangkat tema utama “Momongu Kambungu” yang artinya “Membangun Kampung” dari potensi sumber daya alam yang ada. Berdasarkan hasil survey yang dilakukan potensi desa Tolotio adalah produksi kelapa melimpah, namun saat ini masih menggunakan pengolahan tradisional yang berkualitas rendah serta kadar air yang tinggi. Tujuan pengabdian ini adalah untuk memberikan wawasan dan pengetahuan tentang pengolahan kopra putih yang benar dan memenuhi standar ekspor. Metode kegiatan Pengabdian Masyarakat menggunakan metode ceramah dan demonstrasi. Langkah-langkah kegiatan adalah ceramah untuk menjelaskan cara pengolahan kopra putih dengan menggunakan greenhouse, kelebihan dibandingkan pengolahan kopra hitam sebelumnya yang secara konvensional. selanjutnya dilanjutkan dengan demonstrasi cara pengolahan kopra putih dengan sistem greenhouse